Adverse effects on thyroid of Chinese children exposed to long-term iodine excess: optimal and safe Tolerable Upper Intake Levels of iodine for 7- to 14-y-old children. Issue 5 (20th April 2018) - Chen, Wen; Zhang, Yixin; Hao, Yunmeng; Wang, Wei; Tan, Long; Bian, Jiancao; Pearce, Elizabeth N; Zimmermann, Michael B; Shen, Jun; Zhang, Wanqi
ABSTRACT: Background: The adverse effects of iodine excess on the thyroid in children are not well understood, and the Tolerable Upper Intake Level for iodine in children is unclear. Objective: The aims of this study were to assess the effects of chronic long-term iodine excess on thyroid function in children and to explore the safe Tolerable Upper Intake Level of iodine in Chinese children. Design: A multistage cross-sectional study was conducted in 2224 children from areas with adequate to excessive iodine content in drinking water. Repeated samples of 24-h urine and spot urine samples were collected to estimate habitual daily iodine intakes of children. The thyroid volume in children was measured and blood samples were collected to determine thyroid function. Results: The habitual iodine intake of children was 298 μg/d (range: 186–437 μg/d). The total goiter rate was 9.7%, 232 (11.2%) children had hyperthyrotropinemia, and 232 (11.2%) children had thyroglobulin (Tg) concentrations >40 μg/L. The prevalence of hyperthyrotropinemia was >10% in children at iodine intakes of 200–300 μg/d. Tg concentrations increased with increased iodine intake (β = 0.5; 95% CI: 0.4, 0.6), and the prevalence of Tg >40 μg/L was >3% in all iodine-intake groups. Multivariate logistic regression analysis indicated that the risk of total goiter significantly increased at iodine intakes ≥250–299 μg/d in 7- to 10-y-old children (OR: 8.8; 95% CI: 2.3, 34.0) and at iodine intakes ≥300–399 μg/d in 11- to 14-y-old children (OR: 5.2; 95% CI: 1.5, 18.3). However, there were no consistent differences in the risk of hyperthyrotropinemia and Tg >40 μg/L in children between different iodine-intake groups. Conclusions: Thyroid volume and goiter appear to be more sensitive indicators of thyroid stress than thyrotropin and Tg in children with long-term excess iodine intakes. We recommend 250 and 300 μg/d as safe Tolerable Upper Intake Levels of iodine for children aged 7–10 y and 11–14 y, respectively. This trial was registered at www.clinicaltrials.gov as NCT02915536.